2018
DOI: 10.1098/rsos.181296
|View full text |Cite
|
Sign up to set email alerts
|

Supersaturation with water explains the unusual adhesion of aggregate glue in the webs of the moth-specialist spider,Cyrtarachne akirai

Abstract: Orb webs produced by araneoid spiders depend upon aggregate glue-coated capture threads to retain their prey. Moths are challenging prey for most spiders because their scales detach and contaminate the glue droplets, significantly decreasing adhesion. Cyrtarachne are moth-specialist orb-weaving spiders whose capture threads adhere well to moths. We compare the adhesive properties and chemistry of Cyrtarachne aggregate glue to other orb-weaving spiders to test hypotheses about their structure, chemistry and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(50 citation statements)
references
References 32 publications
(110 reference statements)
0
34
0
Order By: Relevance
“…The aggregate gland glue is composed of adhesive glycoproteins surrounded by an aqueous solution of low molecular mass compounds (LMMCs) 14 . Therefore, the difference in droplet size changes the proportion of water and achieves different viscosity 15 . Spiders that use a dry capture thread with mechanical stickiness instead of the viscid capture silk are called cribellate spiders.…”
Section: Introductionmentioning
confidence: 99%
“…The aggregate gland glue is composed of adhesive glycoproteins surrounded by an aqueous solution of low molecular mass compounds (LMMCs) 14 . Therefore, the difference in droplet size changes the proportion of water and achieves different viscosity 15 . Spiders that use a dry capture thread with mechanical stickiness instead of the viscid capture silk are called cribellate spiders.…”
Section: Introductionmentioning
confidence: 99%
“…Bolas spiders mimic female moth pheromones to attract their male counterparts, which they capture by swinging a single large glue droplet that hangs at the end of a silk strand (Figure 1C) (Eberhard 1977). The remarkable glue of these spiders is able to adhere in spite of a moth’s scales, which easily detach allowing them to escape other forms of predation (Sahni et al 2011b; Diaz et al 2018).…”
mentioning
confidence: 99%
“…However, K(H 2 O) + was not detected in the suspended pristine aggregate glue droplet (Figure 2). Diaz et al reported that water will lose from just made “fresh” aggregate glue droplets even exposure to >90% RH conditions 28 . The “fresh” aggregate glue droplet volume decreased by as much as 90% within 30–60 min, and it is irreversible 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Diaz et al reported that water will lose from just made “fresh” aggregate glue droplets even exposure to >90% RH conditions 28 . The “fresh” aggregate glue droplet volume decreased by as much as 90% within 30–60 min, and it is irreversible 28 . However, water was not completely lost 28 .…”
Section: Resultsmentioning
confidence: 99%